School health care and multiprofessional collaboration in compulsory school – teaching staff’s perceptions - Frida Gädda; Jessica Hemberg; Pia Nyman-Kurkiala (Cogent Education, 2023)
AbstractThe school environment offers a unique platform for health promotion work with children and young people. Increasingly multifaceted health problems among children and young people and their families require investments in multiprofessional collaboration in schools. The aim of this study was to investigate teaching staff’s perceptions of the school nurse’s role in compulsory school and explore multiprofessional collaboration between school health care and teaching staff. Semi-structured interviews were conducted with teaching staff from Finland-Swedish compulsory schools in Finland and qualitative content analysis was used as method. Three main categories and eleven subcategories were found, describing the teaching staff’s views on the role of school health nurses in schools, factors that hinder and promote multiprofessional collaboration, and development proposals for collaboration. The complexity of multiprofessional collaboration in a school context is highlighted. Improved collaboration is important for increasing the chances of finding and helping students and their families early on.